PEMBINAAN KOMPETENSI DOSEN UNTUK MENINGKATKAN PRESTASI MAHASISWA STIT AL-HILAL SIGLI - Abdullah Ali (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2017)
The competence of lecturers as educators has a very good position, which has a direct influence on the learning process, quality of graduates and competitive output patterns. The purpose of this study was to determine the program of coaching, implementation of coaching, and competency development of lecturers to improve undergraduate achievement at the Tarbiyah Al-Hilal Sigli College. This research was conducted at STIT Al-Hilal Sigli. The resource persons consisted of the Chairperson, lecturers and students of STIT Al-Hilal Sigli. This research is descriptive qualitative. The results of the study indicate that the long-term lecturer competency development program includes syllabus development, evaluation of lecturer performance, lecturer development that is relevant to the subjects taught through. The development of lecturer competence, especially by sending lecturers to continue their education to the Masters and Doctoral levels in various universities. The implementation of lecturer competency development is not only focused on further education, but is also carried out through activities by inviting tutors from outside, holding scientific seminars and discussions, comparative studies and partnerships, which are carried out with several Islamic universities, such as IAIN on the Java island. The existence of knowledge that is built positively can add to the experience of lecturers, thereby increasing their competence as teaching staff and educators. Obstacles in developing lecturer competencies, limited student programs, there are still many lecturers who do not master foreign languages, especially Arabic and English.